ADJECTIVAL PHRASEOLOGICAL UNITS EXPRESSING EMOTIONS IN ENGLISH - Kurbanova Dilnoza Arslonovna; Abdalyazova Yulduzoy Kaxramon qizi (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
This article explores adjectival phraseological units expressing emotions in modern English, focusing on their semantic, structural, and functional properties. Phraseological units are fixed combinations of words characterized by stability and idiomatic meaning, and they play a crucial role in conveying emotional states more vividly than single lexical items. The study aims to analyze how such units function as expressive tools in communication and how they reflect cultural and cognitive aspects of emotional perception. The research examines different types of emotional phraseological units, including those expressing positive, negative, and complex emotions. Special attention is given to their metaphorical nature, as many of these expressions are based on conceptual metaphors linking emotions with physical experiences, colors, or spatial orientation. The article also investigates their structural patterns, such as prepositional, comparative, and participial constructions, highlighting their syntactic behavior in sentences.